Analysis of Teacher and Student Understanding of Minimum Competence Asessment (AKM) - Joko Setiono; Bambang Qomaruzzaman; Qiqi Yuliati Zaqiah (Universitas Muhammadiyah Enrekang, 2023)
The aim of this research is to analyze the understanding of teachers and students towards the Minimum Competency Assessment (AKM) as one of the instruments of the National Assessment. The urgency of teachers’ and students’ understanding of the Minimum Competency Assessment will determine the success of the implementation of new policies in the field of learning evaluation. This research uses a quantitative descriptive approach with a survey method through the distribution of questionnaires in the form of a Google Form to teachers and students of 11th grade at State Senior High School 62 in East Jakarta about the essence, competencies, components, format, and number of questions in the AKM. The collected data is then analysed using descriptive statistical techniques in the form of percentages. The results of this research show that 64.7% of teachers have understood the AKM, while 35.5% of teachers have not understood it. Meanwhile, 66.4% of students have understood the AKM, while 33.3% of students have no understood yet